Pengaruh Status Sosial, Keluarga, Situasi dan Kepecayaan Terhadap Keputusan Pembelian Jeruk di Desa Poncokusumo. - Dhani Firmansyah; Mohammad Rizal; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study examines the effect of social status, family, situational factors, and trust on consumers’ purchasing decisions of oranges in Poncokusumo Village. A quantitative approach was applied using survey data collected from 95 respondents selected through purposive sampling. Data were analyzed using multiple linear regression. The results show that social status, family, situational factors, and trust simultaneously and partially have a significant influence on purchasing decisions. These findings indicate that purchasing decisions are influenced by both social and psychological factors, in addition to economic considerations. The study provides insights for local farmers and agribusiness actors to develop more effective marketing strategies for local orange products. Keywords: Social Status, Family, Situational Factors, Trust, Purchasing Decision.